2000
DOI: 10.1123/nirsa.24.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Professional Preparation in Sport Management: A Narrative Meta-Analysis

Abstract: The purpose of the study was to employ a narrative meta-analysis approach to explore the original study and replications of the Recreational Sports Competency Analysis (RSCA) (Jamieson, 1980). Several researchers ((Jamieson, 1980; Ulrich and Parkhouse, 1982; Jennings, 1984; and Parks and Quain, 1986) have documented the importance of sound curriculum development in sport management and resultant curriculum. Two research questions were posed to elicit what aspects might be applicable for comparison and what sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Furthermore, Ross (1990) reported that there were a number of experiences that were essential to future specialists in the field of recreational sports, of which "research or creative projects" was included. Similarly, Jamieson and Toh (2000) developed an instrument to investigate professional preparation in Sport Management. One of the 12 competencies included was "research."…”
Section: Develop and Practice Research Skillsmentioning
confidence: 99%
“…Furthermore, Ross (1990) reported that there were a number of experiences that were essential to future specialists in the field of recreational sports, of which "research or creative projects" was included. Similarly, Jamieson and Toh (2000) developed an instrument to investigate professional preparation in Sport Management. One of the 12 competencies included was "research."…”
Section: Develop and Practice Research Skillsmentioning
confidence: 99%
“…Similarly, Jamieson and Toh developed an instrument to investigate professional preparation in sport management. One of the 12 competencies noted was "research" (Jamieson & Toh, 2000).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Δμ αηηίαο απηνχ, ζε παγθφζκην επίπεδν, ππάξρεη αλάγθε γηα ζπλερή αμηνιφγεζε θαη εηζαγσγή δηαθνξεηηθψλ απφςεσλ κε ζηφρν ηελ αλάπηπμε ησλ θαιχηεξσλ πξνγξακκάησλ νξγάλσζεο-δηαρείξηζεο αζιεηηζκνχ (DeSensi, . (Jamieson & Toh, 2000). (Marsh,1990;PudθAmstrong,1994;Kosar & Hasomeris, 2001).…”
Section: Meρο η κδφαλαηο νunclassified